PENGENDALIAN PENYAKIT BUSUK BUAH KAKAO DENGAN PESTISIDA NABATI - SUDARMA, I MADE; SUPRAPTA, D. N. (AGRITROP; Vol. 28, No. 1 Maret 2009)
Pod rot disease in Cacao (Theobroma cacao) caused by Phytophthora palmivora has been known to cause serious damage at cacao-growing area in the world. The disease can cause crop loss until 90%. Hitherto cacao farmer controls disease only on usage of synthetic pesticide. Therefore important is performed a operation research of disease with other alternative, like usage of leaf extract Piper betle and clove flowers (Eugenia caryophillata), as botanical pesticide. Research has been conducted in Pulukan village, Sub-Province Jembrana in January until April 2006, to study botanical pesticide effectivity (plant extract) to control pod rot disease. Research applies completely randomized block design, with four treatments and six replications, causing is required 24 experiment units. Every re-attempt unit thrice and ten tree pears observed as sample. Disease percentage is observed every one week once in each treatment. Results of the experiment indicated that leaf extract of P. betle and clove flowers effective controls pod rot disease (alone or in combination). The extract mixture P. betle and clove flower (combination) can suppress disease until 64,57 %, clove flowers extract (alone) 33,33% and synthetic pesticide (Dithane M45) equal to 60,40%. Result of this depicts treatment tested is usable to reduce pathogen pod rot disease of cacao.
Keywords: Pod rot disease, Piper betle, Eugenia caryophillata, Phytophthora palmivora.